2014
DOI: 10.3892/mmr.2014.2036
|View full text |Cite
|
Sign up to set email alerts
|

F-actin cytoskeleton reorganization is associated with hepatic stellate cell activation

Abstract: The activation of hepatic stellate cells (HSCs) is involved in the development of hepatic fibrosis. Previous studies have indicated that the acquisition of certain properties by activated HSCs is highly dependent on the reorganization of the actin cytoskeleton. However, direct evidence showing that the reorganization of the actin cytoskeleton is responsible for HSC activation is lacking. The aim of the present study was to investigate the role of cytoskeletal reorganization during HSC activation and to clarify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 23 publications
(21 reference statements)
3
22
0
Order By: Relevance
“…Actin is present in the cytoplasm as a monomeric G‐actin or as a reversibly assembled polymeric F‐actin filament. G‐actin molecules polymerize into F‐actin when their concentration increases (Cui et al ., ). This result represents that cytoskeleton was in a state of being remodelled, in which actin monomeric G‐actin was highly increased in the cytoplasm.…”
Section: Discussionmentioning
confidence: 97%
“…Actin is present in the cytoplasm as a monomeric G‐actin or as a reversibly assembled polymeric F‐actin filament. G‐actin molecules polymerize into F‐actin when their concentration increases (Cui et al ., ). This result represents that cytoskeleton was in a state of being remodelled, in which actin monomeric G‐actin was highly increased in the cytoplasm.…”
Section: Discussionmentioning
confidence: 97%
“…In vivo, an activation of hepatic stellate cells can finally lead to the disease state of hepatic fibrosis. It was previously reported that F-actin cytoskeletal reorganization is an essential step in the activation of hepatic stellate cells (Cui et al, 2014). The cell model might therefore also be suitable to determine if and how substances alter the activation state and thereby a disease progression.…”
Section: Discussionmentioning
confidence: 99%
“…HSCs respond to VEGF produced by tumor-activated cells and migrate to the sites of angiogenesis (109). The p38 mitogen-activated protein kinase (MAPK) pathway has been recently proposed as a mediator of endothelial cell activation, cytoskeletal reorganization and migration of HSCs (110,111). Interestingly, ICAM-1 activation has been shown to stimulate the p38 MAPK pathway in endothelial cells, astrocytes and renal fibroblasts (112)(113)(114).…”
Section: Tumor Cell Extravasation: Opening the Liver's Doors To Invadmentioning
confidence: 99%